2013
DOI: 10.1080/15389588.2012.688152
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclist–Bicyclist Crashes—A Medical and Technical Crash Analysis

Abstract: The prevalence of bicycle-to-bicycle crashes is high. Most of these accidents occur in urban areas. Bicyclists should be considered as minimally or unprotected road users, with an unsatisfactorily low rate of helmet use. Though the average level and patterns of injuries is moderate, most of the severe injuries involved the head and extremities. However, there was no significant correlation between frequent helmet use and sustained injuries to the head of major AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By taking into account the systematic heterogeneity in bicycle crashes, researchers and practitioners can identify the most appropriate safety countermeasures for different bicycle crash types occurred under different conditions. To reduce heterogeneity, researchers focused on narrow bicycle crash characteristics such as type of opponent vehicle [ 54 ] or type of location [ 55 ]. Although the findings of these studies are important to identify the risk factors and the appropriate safety countermeasures by reducing heterogeneity, this approach does not guarantee that bicycle crashes data comprise homogeneous groups of bicycle crashes.…”
Section: Introductionmentioning
confidence: 99%
“…By taking into account the systematic heterogeneity in bicycle crashes, researchers and practitioners can identify the most appropriate safety countermeasures for different bicycle crash types occurred under different conditions. To reduce heterogeneity, researchers focused on narrow bicycle crash characteristics such as type of opponent vehicle [ 54 ] or type of location [ 55 ]. Although the findings of these studies are important to identify the risk factors and the appropriate safety countermeasures by reducing heterogeneity, this approach does not guarantee that bicycle crashes data comprise homogeneous groups of bicycle crashes.…”
Section: Introductionmentioning
confidence: 99%
“…There is plethora of evidences in the literature that helmet reduces the risk of loss of consciousness and head injury. [2223] Policy changes and educational programs that increase the use of helmets may prevent deaths. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Among children aged 5–14, who have the highest rate of bicycle-related injuries, 29% never wore a helmet while riding [ 18 ]. Bicycle-to-bicycle collisions have also been found to be prevalent, especially in urban environments [ 19 ]. Although these injuries tend to be more moderate, severe injuries can occur to the head or other extremities [ 19 , 20 ].…”
Section: The Importance Of Booster Seats and Bicycle Helmetsmentioning
confidence: 99%
“…Bicycle-to-bicycle collisions have also been found to be prevalent, especially in urban environments [ 19 ]. Although these injuries tend to be more moderate, severe injuries can occur to the head or other extremities [ 19 , 20 ]. Recent research examining the risk of fatal head injuries found that not wearing a helmet while riding a bicycle increased the risk of sustaining a head injury, as well as the risk of death from such an injury [ 21 ].…”
Section: The Importance Of Booster Seats and Bicycle Helmetsmentioning
confidence: 99%